Disappearance of 125I-labelled and unlabelled insulins from blood in normal and injured rats. - Frayn, K (1976)
1. The disappearance from blood of either 125I-labelled bovine insulin or unlabelled rat insulin after a single intravenous injection has been studied in rats. 2. The disappearance of the labelled insulin was slower than that of native insulin. 3. Ether anaesthesia produced a significant impairment, and bilateral nephrectomy a very marked impairment, of disappearance of the labelled insulin, suggesting that changes in the removal of this tracer may nevertheless parallel changes in the metabolism of native insulin. 4. Simultaneous intravenous injection of unlabelled bovine insulin (1 unit/kg) did not affect disappearance of the labelled insulin. 5. A 20% full-thickness scald injury, produced 2 h previously, had no significant effect on disappearance of the labelled insulin, either with or without the simultaneous administration of unlabelled bovine insulin. 6. The disappearance of unlabelled rat insulin from plasma was also similar in control and scalded rats. 7. It was concluded that the half-life of plasma insulin in the rat, as estimated by either of the techniques used, is not significantly affected by this severe non-haemorrhagic injury.